The impact of hospital accreditation on patient safety culture in the health services implementation at Sanglah General Hospital, Bali - Indrayani, Putu May; Januraga, Pande Putu; Negara, Surya (Public Health and Preventive Medicine Archive, 2021)
Background and purpose: Hospital accreditation is carried out to evaluate hospitals’ performance in providing patients with excellent and safe health services. One aspect of service quality is patient safety culture. This study aims to determine the impact of hospital accreditation on patient safety culture in health service implementation at the Sanglah General Hospital in Denpasar City, Bali Province. Methods:This study used a qualitative research design. In-depth interviews were conducted to 11 informants consisting of hospital management, clinicians and nurses which were chosen purposively since they were directly related to the assessment and supervision of health service providers at Sanglah Hospital. The interview guide was based on the Modified Manchester Patient Safety Framework (MaPSaF). Data were analyzed with a thematic approach. Results: The interview results show that the ten dimensions of patient safety culture had been implemented well but still need to be improved in the dimensions of giving priority to safety, system errors and responsibilities, recording incidents and best practices, learning and influencing change, also education and training of staff and teamwork. The maturity level of patient safety culture at Sanglah Hospital is at generative culture in four dimensions and at proactive culture on the six dimensions of patient safety culture. Conclusion: Accreditation had a positive impact on the maturity level of patient safety culture at a proactive level, mainly changes in knowledge, attitudes, and behavior in health service providers. However, in its implementation, there were still constrained on infrastructure, time, and energy.